EXPECTATIONS IN RESPECT OF THE SUPERVISOR‘S IMAGE: THE LITHUANIAN CASE - Merfeldaitė, Odeta; Sadauskas, Justinas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Each profession and the image of its representatives are being assessed taking into consideration the specifics of the activity, the environment, the existing stereotypes and the attitudes towards it. The activity of the supervisor is a new one in Lithuania therefore a lot of stereotypic attitudes appear in respect of the supervisor‘s profession. That means it is very important to find out what supervisor’s image have the supervisors themselves, and what are the expectations of the counselled ones in respect of the professionals in this field. The goal of the research is to analyse the expectations in respect of the supervisor in Lithuania, based on insights of supervisors and of the persons with and without the experience of supervision.